Chalcogen Chemistry 2019
DOI: 10.5772/intechopen.78647
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sulfur-Related Species in Oxygen Reduction Reactions

Abstract: Heteroatom (metal and nonmetal) doping is essential to achieve excellent oxygen reduction reaction (ORR) activity of carbon materials. Among the heteroatoms that have been studied to date, sulfur (S) doping, including metal sulfides and sulfur atoms, has attracted tremendous attention. Since S-doping can modify spin density distributions around the metal centers as well as the synergistic effect between S and other doped heteroatoms, the S-C bond and metal sulfides can function as important ORR active sites. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…[28,29] Various nitrogen and sulphur species can be incorporated into the graphitic network, including pyridinic, pyrrolic, graphitic (quaternary) and thiol groups, further enhancing their catalytic activity. [19,[30][31][32][33][34] Following the pioneering work of Hu et al [35] and Girault et al [12] our group have demonstrated that hybrids composed of the molybdotungstophosphate polyoxometalate (P 2 W 12 Mo 6 ) considered in this work immobilised in nitrogen and sulphurdoped carbon nanomaterials are active catalysts for the oxygen reduction reaction on modified electrodes. Herein, we report on the preparation of composites based on the incorporation of the Wells-Danson POM's salt K 6 • α-[P 2 W 12 Mo 6 O 62 ] • 19H 2 O onto distinct nitrogen and sulphur-doped carbon materials (sulphurdoped graphene flakes and multi-walled carbon nanotubes, nitrogen-doped multi-walled carbon nanotubes) and their application as ORR electrocatalysts.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…[28,29] Various nitrogen and sulphur species can be incorporated into the graphitic network, including pyridinic, pyrrolic, graphitic (quaternary) and thiol groups, further enhancing their catalytic activity. [19,[30][31][32][33][34] Following the pioneering work of Hu et al [35] and Girault et al [12] our group have demonstrated that hybrids composed of the molybdotungstophosphate polyoxometalate (P 2 W 12 Mo 6 ) considered in this work immobilised in nitrogen and sulphurdoped carbon nanomaterials are active catalysts for the oxygen reduction reaction on modified electrodes. Herein, we report on the preparation of composites based on the incorporation of the Wells-Danson POM's salt K 6 • α-[P 2 W 12 Mo 6 O 62 ] • 19H 2 O onto distinct nitrogen and sulphur-doped carbon materials (sulphurdoped graphene flakes and multi-walled carbon nanotubes, nitrogen-doped multi-walled carbon nanotubes) and their application as ORR electrocatalysts.…”
Section: Introductionmentioning
confidence: 82%
“…By introducing nitrogen and sulphur into the sp 2 carbon structure, the electronic properties of the original carbons can be enhanced, resulting in improved electrocatalytic performance for ORR [28,29] . Various nitrogen and sulphur species can be incorporated into the graphitic network, including pyridinic, pyrrolic, graphitic (quaternary) and thiol groups, further enhancing their catalytic activity [19,30–34] …”
Section: Introductionmentioning
confidence: 99%
“…Recently, carbonaceous catalysts have emerged as a new frontier in the electrocatalysis field owing to their feasible synthesis, high conductivity, and low cost. , The development of efficient OER and HER catalysts via single-atom doping or codoping of two or more nonmetallic heteroatoms has shown considerable promise in this regard; in particular, the incorporation of N and S into a carbon matrix has resulted in electrocatalysts that exhibit enhanced OER and HER kinetics. In the case of N-doping, this observation originates from the higher electronegativity of N (3.04) in comparison to that of carbon (2.55), which increases the positive charge on adjacent C atoms in the material matrix.…”
Section: Introductionmentioning
confidence: 99%